Bomebesin: specific binding to rat brain membranes. - Moody, T W (1978)
The binding of a radiolabeled bomebesin analogue to rat brain membranes was studied. [125I-Tyr4]Bombesin bound with high affinity (KD = 3 nM) to a single class of non-interacting sites. Binding was specific, saturable (3.8 pmol of sites/g of wet tissue), and reversible. Regional and subcellular distribution studies showed that the density of sites was 7-fold greater in the hippocampus than the medulla/pons and greater in synaptosomal fractions than in mitochondrial or nuclear fractions. The abilities of numerous bombesin analogues to induce hypothermia and to inhibit [125I-Tyr4]bombesin-binding activity correlate well. Numerous amino acid residues near the CONH2-terminal are required for high-affinity binding and biological potency.